The lower limit for meter in dance drumming from West Africa - Polak, Rainer (Empirical Musicology Review, 2018)
Human rhythm perception and sensorimotor synchronization are both constrained by temporal thresholds on several levels. The lower limit for durations that allow for entrainment at the level of metric beat subdivision has been estimated at about 100–120 ms (London, 2002; Repp, 2003). Tempos and subdivision durations reported for American jazz and East African xylophone music performance, however, suggest that the perception of shorter subdivisions within a range of 80–100 ms may well be possible. This paper musicologically analyzes and empirically measures the fastest metric subdivisions in two sets of live recordings of vernacular dance music from West Africa. In two recordings of Ewe drumming from Ghana, subdivision durations display mean values within a range of 90–100 ms for extended periods of time. Four recordings of jembe drumming from Mali feature subdivision IOIs of about 80–90 ms during their final and fastest sections. A lower limit for metric subdivision durations is hypothesized to perceptually constrain West African drumming within a threshold range of about 80–100 ms.